Chemopreventive effects of mate against mouse mammary and colon carcinogenesis - Zapaterini, Joyce R. [UNESP]; Bidinotto, Lucas T. [UNESP]; Rodriguues, Maria A. M. [UNESP]; Barbisan, Luís F. [UNESP] (Human & Experimental Toxicology, 2010)
The present study evaluated the chemopreventive potential of mate tea-like intake on mammary and colon carcinogenesis initiated by 7,12-dimethylbenz(a)antracene (DMBA) and 1,2-dimethylhydrazine (DMH) in female Swiss mice. After the initiation period, the animals received basal diet and organic mate tea-like, conventional mate tea-like, or green tea (positive control) at 2.0% as the drinking fluid during 15 weeks. At week 20, colon and mammary gland were analyzed for preneoplastic and neoplastic lesions development. Colon and mammary gland complexes were processed for cell proliferation analysis, estimated by proliferating cell nuclear antigen labeling index (PCNA-LI%). Specially, organic mate tea-like reduced the values of PCNA-LI% in colonic crypts (p < .003) and in mammary glands (p < .05) in DMBA/DMH-initiated groups. A lower incidence of aberrant crypt foci (ACF) in colon (p = .03) and of hyperplastic and neoplastic lesions in mammary gland (p < .05 and p < .02, respectively) was observed in DMBA/DMH-initiated groups treated with organic mate tea-like. These results suggest that post-initiation treatment with organic mate tea-like inhibited the development of colon and mammary carcinogenesis in a two-step medium-term mouse carcinogenesis model.
Keywords: Female Swiss mice; Mammary and colon carcinogenesis; Ilex paraguariensis chemoprevention